2019
DOI: 10.1115/1.4042756
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Evolution of Tip Leakage Vortex in a Mixed-Flow Pump With Tip Clearance

Abstract: Tip clearance in pump induces tip leakage vortex (TLV), which interacts with the main flow and leads to instability of flow pattern and decrease of pump performance. In this work, the characteristics of TLV in a mixed-flow pump are investigated by the numerical simulation using shear stress transport (SST) k–ω turbulence model with experimental validation. The trajectory of the primary tip leakage vortex (PTLV) is determined, and a power function law is proposed to describe the intensity of the PTLV core along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 30 publications
0
56
0
Order By: Relevance
“…e flow pattern, especially vortex structures like tip leakage vortex, is of crucial importance to the performance of waterjet pump. Liu and Tan [29,30] and Hao and Tan [31] have done a lot of research on the evolution and development of tip leakage vortex and obtained a number of useful results which can provide theoretical guidance for the further study of tip leakage vortex. e inlet passage is used as an overflow passage connecting the propulsion pump and the bottom of the propulsion ship.…”
Section: Introductionmentioning
confidence: 99%
“…e flow pattern, especially vortex structures like tip leakage vortex, is of crucial importance to the performance of waterjet pump. Liu and Tan [29,30] and Hao and Tan [31] have done a lot of research on the evolution and development of tip leakage vortex and obtained a number of useful results which can provide theoretical guidance for the further study of tip leakage vortex. e inlet passage is used as an overflow passage connecting the propulsion pump and the bottom of the propulsion ship.…”
Section: Introductionmentioning
confidence: 99%
“…On contrary, the k-ω turbulence model under low Reynolds number is applied in the region close to the wall when F 1 = 1. As a result, the SST k-ω turbulence model are believed to be able to provide a relatively high prediction accuracy of the performance curves of pump with acceptable computational cost [27,28].…”
Section: Turbulence Modelmentioning
confidence: 99%
“…Both experimental and numerical approaches have been used to study compressor flow, with and without IGVs. Both can give valuable insight; however, both have their limitations.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have applied CFD simulations to investigate features such as performance, 7,8 unsteady interactions between the IGVs and the impellers, 9,10 pressure fluctuations at large IGV angles, 11 and the effect of IGV geometry. 1,12 A review of preswirl in from IGVs can be found in the work of Liu et al 13 Both experimental [14][15][16] and numerical 3,9,[17][18][19][20][21][22] approaches have been used to study compressor flow, with and without IGVs. Both can give valuable insight; however, both have their limitations.…”
Section: Introductionmentioning
confidence: 99%